Effect of nanometric γ′-particles on the stress-induced martensitic transformation in 〈001〉-oriented Co49Ni21Ga30 shape memory alloy single crystals. (15th July 2019) - Lauhoff, C.; Reul, A.; Langenkämper, D.; Krooß, P.; Somsen, C.; Gutmann, M.J.; Kireeva, I.; Chumlyakov, Y.I.; Schmahl, W.W.; Niendorf, T.
Abstract: The effect of finely dispersed particles on the functional properties and morphology of thermally induced martensite in Co-Ni-Ga shape memory alloys has been already reported in literature, however, still important aspects are not fully understood. The current study focuses on the stress-induced martensitic transformation of solution-annealed, i.e. precipitate-free, and aged 〈001〉-oriented single crystals. In situ optical microscopy and neutron diffraction experiments show a significant influence of γ′-particles on the martensite variant selection and its morphology under pseudoelastic deformation. In addition, the results reveal detwinning upon loading in the presence of nanometric particles, which is experimentally proven for the first time. Graphical abstract: Unlabelled Image